Development of A Combination of Red Ginger, Cinnamon, and Honey as Antioxidant Functional Drinks - Wijaya, Audrey Salsa (Sport and Nutrition Journal, 2024)
Background: Analyzing antioxidant activity to determine its ability as an anti-radical and test panelists' preference for taste, aroma, and color parameters. Methods: This type of research is an experimental design with a completely randomized design (RAL) with 3 factorial formulations with comparisons of red ginger and cinnamon F1 (25: 25), F2 (25: 50), and F3 (50: 25). Antioxidant activity test by DPPH method and panelists preference by hedonic test. Statistical analysis of hedonic using SPSS with Kruskal Wallis test (α≤0.05) and Mann Whitney follow-up test. Results: Antioxidant activity of F1(73,41%), F2(74,26%) and F3(60,42%). The panelists' best preference was on the F1(25:25) formulation for the taste parameter 3.17; 3.37 fragrance and 3.1 color in the like category. There was a significant difference in the hedonic assessment of the taste and aroma parameters (p= 0.000 < 0.05), but there was no significant difference in the color parameter (p = 0.869 > 0.05). Conclusion: The overall antioxidant activity of the formulation was said to be active as antiradical (% inhibition 50%).